Ethnic and Religious Discrimination in the Wedding Venue Business: Evidence from Two Field Experiments in Germany and Austria - Sarah Carol; Coco Kuipers; Philipp Koesling; Milan Kaspers (Social Problems, 2021)
We add to the current debate on ethno-religious discrimination by studying to what extent discrimination in the wedding venue business is based on religious or ethnic grounds. Do the two reinforce each other? Does the explicit mentioning of a non-religious wedding help to reduce ethnic discrimination in a secularized society? We draw on two field experiments in Germany and Austria. We sent 805 valid emails to wedding venues. We randomly varied two traits, the names (Arabic-origin and native-origin) and whether the wedding was religious (Islamic or Free Church) or not. Using linear probability models and ordinary least squares regressions, we predicted the likelihood of receiving a confirmation, the response time from venues, the length, formality, and tone of the emails as well as the prevalence of mistakes in the emails. Our analyses showed that couples with Arabic-origin names, celebrating an Islamic wedding, received significantly fewer confirmations compared to couples with native-origin names. Celebrating a non-religious wedding of couples with Arabic-origin names reduced the disadvantage. The study suggests statistical discrimination based on religiosity that is inferred from Arabic-origin names.
Keywords: 300; discrimination; Islam; religion; Europe; weddings